NEEDS AND UTILIZATION OF DRUG-INFORMATION RESOURCES OF HEALTHCARE PROVIDERS IN AN ACADEMIC TERTIARY CARE CENTER - ALAKEEL, YOUSIF S.; ALMUTAIRI, DIYANA; LAYQAH, LAILA (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: To investigate the drug-related information needs of healthcare providers (HCPs), their utilization of drug information resources as well as the main factors influencing the selection of resources. Methods: A total of 393 HCPs were conveniently selected and invited to complete a questionnaire. Stratified sampling was used for the three subpopulations of physicians, pharmacists, and nurses. The questionnaire was coded, validated, and analyzed using the Statistical Package for the Social Sciences (SAS version 9.2). Results: Of 450 HCPs approached, 393 completed the questionnaire (response rate 87%). Information related to drug dosage/administration, indications, and interactions is the most frequently required, 47%, 44%, and 34%, respectively. The majority of the sample perceived the Internet (69.47%) and electronic databases (67.43%) as “very useful.” Printed materials (46.56%) and Personal Digital Assistants (PDAs) (44.78%) or calling the pharmacy (43.26%) were also useful resources of information followed by using electronic books and journals (38.42%) and asking colleagues (32.32%). The majority (53.18%) described consulting a clinical pharmacist as “very useful.” However, 16% of the nurse group and 35% of the physician group were not aware of the existence of the Drug Information Center (DIC) and more than 8% of the participants consider calling the DIC about drug-related information “not useful”. Conclusion: Digital resources are used by HCPs more frequently than traditional resources, consulting a clinical pharmacist or calling the DIC. Providing reliable electronic resources and raising the awareness of HCPs regarding the role of a clinical pharmacist and DIC for patient-specific therapies should be instituted.